Black-Scholes Model in Determining European Option Prices on Netflix,Inc. - Desty A. Tambingon; Jullia Titaley; Tohap Manurung (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2019)
Research has been conducted to compare the prices of European option on the Yahoo Finance website with prices obtained from the Black-Scholes model (theoretical price). Data was taken on January 31, 2019 which included the daily share price of Netflix, Inc. (NFLX) on February 14, 2018 - January 31, 2019 to obtain volatility, and NFLX options data due on January 17, 2020. Options with prices lower than theoretical prices are said to be underpriced, so the decision taken is to buy the options. Whereas options with prices higher than theoretical prices are said to be overpriced, so it has to be reconsidered. The proportion of the underpriced call options for the total number of call options is 77.7778%, while the proportion of the underpriced put options for the total number of put options is 38.5714%.